Making Public Sector Reforms Work : Political and Economic Contexts, Incentives, and Strategies - Bunse, Simone; Fritz, Verena (World Bank, Washington, DC, 2012)
Supporting effective public sector reform is a major challenge that the World Bank and other agencies and stakeholders have been grappling with. It is increasingly recognized that political economy factors play a crucial role. However, beyond this broad proposition, specific questions arise: What country contexts are more/less propitious for public sector reforms and what reforms are likely to succeed where? And can more explicitly taking political economy challenges into account help to pursue public sector reforms even in less propitious contexts? This paper addresses these issues in two ways: first, it draws on the existing literature to identify key propositions about factors that can trigger or facilitate public sector reforms, and those that tend to work against (successful) reforms. Second, it investigates the experience of World Bank public sector operations over the decade 2000-2010. It finds that governments in many developing countries face incentives to initiate public sector reforms, but that at the implementation stage, political costs frequently outweigh potential gains; and hence reforms are abandoned or left to wither. Real breakthroughs have been achieved in countries experiencing major structural shifts and those having political leadership committed to higher-level goals. The review of operations shows that successful projects are significantly more widespread than the literature would lead to assume. Furthermore, it provides tentative evidence that investing in understanding political economy drivers has been associated with better project performance. Key implications are the need to differentiate between country contexts more clearly ex ante, concentrate more on reform implementation during windows of opportunity that are typically of limited duration, and design reforms with a clear plan of engagement with stakeholder incentives.